Measuring physical activity in pregnancy using questionnaires: a meta-analysis - Snježana Schuster; Iva Šklempe Kokić; Joško Sindik (Acta Clinica Croatica, 2016)
Physical activity (PA) during normal pregnancy has various positive effects on pregnant women’s health. Determination of the relationship between PA and health outcomes requires accurate measurement of PA in pregnant women. The purpose of this review is to provide a summary of valid and reliable PA questionnaires for pregnant women. During 2013, Pubmed, OvidSP and Web of Science databases were searched for trials on measurement properties of PA questionnaires for pregnant population. Six studies and four questionnaires met the inclusion criteria: Pregnancy Physical Activity Questionnaire, Modified Kaiser Physical Activity Survey, Short Pregnancy Leisure Time Physical Activity Questionnaire and Third Pregnancy Infection and Nutrition Study Physical Activity Questionnaire. Assessment of validity and reliability was performed using correlations of the scores in these questionnaires with objective measures and subjective measures (self-report) of PA, as well as test-retest reliability coefficients. Sample sizes included in analysis varied from 45 to 177 subjects. The best validity and reliability characteristics (together with effect sizes) were identified for the Modified Kaiser Physical Activity Survey and Pregnancy Physical Activity Questionnaire (French, Vietnamese, standard). In conclusion, assessment of PA during pregnancy remains a challenging and complex task. Questionnaires are a simple and effective, yet limited tool for assessing PA.